Implementasi Metode Promethee Dalam Menentukan Kenaikan Jabatan Pada Nuansa Agung Garment - Rosmiati, Mia (POLITEKNIK NEGERI JAKARTA, 2022)
Employee performance in a company has a considerable impact on the development of the company. Companies need employees who are competent, loyal, and qualified. A promotion can be a way for companies to motivate their employees. However, the company has difficulty in selecting suitable employees to be given a higher position. There is still a subjective assessment of employees is a problem that often occurs in a company. This results in jealousy among employees. A decision support system can be a way to determine an employee's promotion. The method used in this study is the Promethee method, which is a fairly good method applied in determining employee promotions. By applying this method, it can help Nuansa Agung Garment companies in selecting employees for promotions and providing convenience in generating alternative solutions in determining promotions. The results obtained from the 15 alternatives used are alternative A11, namely Reka Kasih Sella Wati which is ranked first. Based on the calculation of the four criteria used, namely work attitude, intelligence, performance, and length of work. Alternative A11 obtained the highest result, namely 0.8571. Determination of employees who are recommended to be promoted using the Promethee method provides benefits for the company where employee assessments become more objective, transparent, effective, and efficient